OBESITIES RELATIONS AND CONCEPTS OF APPLICATIONS IN OUR SOCIETY (Fiep Bulletin - online, 2016)
In this article we will study and investigate concepts of BMI (Body Mass Index) which means body mass index and that it is a measure of the level of fat each person is an average of international benchmark recognized by the WHO (World Health Organization Cheers). This article aimed to search for family members and close friends. This is a quantitative research descriptive, where the work was first started with our relatives, neighbors, close friends, co-workers and school. 129 people were investigated, 64 females, between 15 and 39 years old, with a mean of 21 years and 65 males, between 15 and 39 years of age, averaging 23 years. Through these results, we can see that much of the population investigated, okay, for obesities and its risks, as metabolic problems. But still there are people with some problems and coronary risk and solutions can be taken to these people as a nutritional medical supervision, regulation of physical activity, a balanced diet and especially the monitoring of a professional physical education because we know that with a multidisciplinary team can make the prevention of such diseases such as obesity.
Keywords: Obesity; BMI; WHR